Réponses

2014-10-22T18:27:21+02:00
Développer et réduire A = 2x - [3x - (7 + 5x)]
A = 2x - (3x - 7 - 5x)
A = 2x - 3x + 7 + 5x
A = 4x + 7

B = 3 - 5 (5x - 2) - 4x
B = 3 - 25x + 10 - 4x
B = - 29x + 13

C = (2x - 3) (x + 1) + 5(x + 4)
C = 2x² + 2x - 3x - 3 + 5x + 20
C = 2x² + 4x + 17

D = 3x²  - (2x - 4) (5x - 7)
D = 3x² - (10x² - 14x - 20x + 28)
D = 3x² - 10x² + 14x + 20x - 28
D = - 7x² + 34x - 28
2014-10-22T18:29:12+02:00
A = 2x-[3x-(7+5x)]
= 2x -(3x - 7 -5x)
= 2x -(-2x -7)
= 2x+2x+7
= 7

B = 3-5(5x-2)-4x
= 3 - 25x+10 -4x
= -29x+13

C = (2x-3)(x+1)+5(x+4)
= 2x² +2x -3x -3 +5x +20
= 2x²+4x +17

D = 3x( puissance 2) -(2x-4)(5x-7)
= 3x
²- (10x² -14x -20x+28)
= 3x²-10x²+34x -28
= -7x²+34x -28